Assessing the Effectiveness of Disaster-Resilient Villages in Flood Mitigation: A Case Study of Tanete Riaja District - Rezky Nur Padhilah; Muliana (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal